2017
DOI: 10.1016/j.chemosphere.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Serum perfluoroalkyl acids (PFAAs) and associations with behavioral attributes

Abstract: The ubiquitous use of poly- and perfluoroalkyl substances (PFASs) in a variety of industrial and consumer products has resulted in chronic exposure in most industrialized nations, and led to measurable concentrations in blood and other tissues in humans across all life stages; however, behavioral attributes that relate to exposure are not well studied. To further investigate how behavior may relate to PFAS exposure, 37 adults were recruited from central North Carolina. Participants provided blood samples and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…A recent study of Boston area children found elevated PFOS, PFHxS and N-MeFOSAA in sera from individuals who sleep in a room with carpet or a rug [ 60 ]. Other studies have found positive associations between PFOS and PFHxS and use of stain-repellant clothing, firefighting foams and consumption of microwavable foods and negative associations between PFHxS and vacuuming frequency [ 72 , 73 ]. Data linking consumer product use to serum PFAS levels are scarce due to challenges associated with quantifying long-term user behavior.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of Boston area children found elevated PFOS, PFHxS and N-MeFOSAA in sera from individuals who sleep in a room with carpet or a rug [ 60 ]. Other studies have found positive associations between PFOS and PFHxS and use of stain-repellant clothing, firefighting foams and consumption of microwavable foods and negative associations between PFHxS and vacuuming frequency [ 72 , 73 ]. Data linking consumer product use to serum PFAS levels are scarce due to challenges associated with quantifying long-term user behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PFHxS was detected in low concentrations in a variety of species; however, PFHxA levels are often below the limit of detection in environmental tissue samples (Kannan et al 2005;Sedlak et al 2017). Detection of these compounds in humans has been reported (Lewis et al 2015;Olsen et al 2017;Perez et al 2013;Siebenaler et al 2017), but due to increasing concerns of the bioaccumulation and toxicity associated with PFHxS, serum levels of this compound have plateaued (Land et al 2018). PFHxA was reported in fish fillet collected from the Mississippi in 9-15% of samples at concentrations ranging from 0.12-0.18ng/g, depending on species, and PFHxS in 7-55% of samples ranging from 0.032 -0.069 ng/g (Newsted et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…PFHxS and PFOS are long-chained perfluoroalkyl sulfonate analogs with the longest half-lives in human serum [45], which may increase the likelihood of bioaccumulation. PFOS and PFHxS have been associated with certain exposure sources including aqueous film forming foams, microwaveable food, and waterproof clothing [46][47][48]. Sources of exposure to carboxylic acids are diverse, though indirect sources include oil-and water-repellant applications of fluorotelomer alcohols and polyfluoroalkyl phosphate esters [49].…”
Section: Discussionmentioning
confidence: 99%